Decision of Staying Active to Re-Study as the Implication of Quality, Orientation, and Services Costs Mediated by Student Satisfaction and Word of Mouth - Maya Dora, Yenny; Kartini Yahya, Dwi; Effendi, Nury; Prabowo, Harjanto (International Journal of Engineering and Technology, 2018)
The growth and development of Private University is strongly influenced by the large number of students who are studying at Private University. This is because the fund that is needed to fund all the activities of Private University are sourced from the students. The more students who actively study the more rapid the growth and development of Private University will be. This study aims to analyze the student decisions of Staying Active to re-study is an implication of Service Quality, Service Orientation, Service Costs which are mediated by Student Satisfaction and Word of Mouth. This study was conducted on Private University students in West Java. The method in this study is the survey method where the data is obtained by the distribution of questionnaires to students. The population of this study is private university students in West Java who have been studying in semester 2. With a sample size of 350 students. This study data is analyzed by using Structural Equation Modeling (SEM) with AMOS 18 program.   This study uses 6 (six) variables altogether, they are Service Quality, Service Orientation, Service Cost, Student Satisfaction, Word of Mouth and Decision of Staying Active to Re-Study. This study will test Service Quality, Service Orientation, Service Costs can directly influence student decisions of staying active to re-study or it is need a mediation of student satisfaction and word of mouth.